2021
DOI: 10.1038/s41598-020-79933-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular twist by 3D ballistocardiography and seismocardiography compared with 2D STI echocardiography in a context of enhanced inotropism in healthy subjects

Abstract: Ballistocardiography (BCG) and Seismocardiography (SCG) assess the vibrations produced by cardiac contraction and blood flow, respectively, by means of micro-accelerometers and micro-gyroscopes. From the BCG and SCG signals, maximal velocities (VMax), integral of kinetic energy (iK), and maximal power (PMax) can be computed as scalar parameters, both in linear and rotational dimensions. Standard echocardiography and 2-dimensional speckle tracking imaging echocardiography were performed on 34 healthy volunteers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…These metrics have shown to be reproducible ( 21 ). Differences in iK metrics have been associated with differences in SV, LVEF, and cardiac output (CO) in healthy subjects during a dobutamine-induced hemodynamic increase ( 19 , 22 ), with an increase during voluntary apnea ( 23 ) and obstructive apnea ( 24 ), and with a surge during sympathetic activation ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…These metrics have shown to be reproducible ( 21 ). Differences in iK metrics have been associated with differences in SV, LVEF, and cardiac output (CO) in healthy subjects during a dobutamine-induced hemodynamic increase ( 19 , 22 ), with an increase during voluntary apnea ( 23 ) and obstructive apnea ( 24 ), and with a surge during sympathetic activation ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…We have earlier shown that a smartphone application using MCG is a clinically useful methodology for the screening of atrial fibrillation and yields better diagnostic accuracy than currently available wearable devices using photoplethysmography signal [6]. Previous research has demonstrated that waveforms derived from seismocardiography and gyrocardiography reproduce the main events seen in left ventricular twist and strain rates obtained from echocardiography [3,7]. Experimental evidence also suggests that abnormalities in the heart function caused by myocardial infarction could be detected using this technology [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that the proposed system empower the healthcare providers and patients to remotely monitor the real-time abnormalities of cardiac health. In [75], SCG and BCG were used for assessing the twist mechanics of left ventricle.…”
Section: Recent Workmentioning
confidence: 99%